Rancang Bangun Aplikasi Monitoring Konsumsi Energi Listrik 1 Fasa Pelanggan Pln Pascabayar Berbasis Web Server - Irawan, Muhamad Angga; Ervianto, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Electricity is one of the sources of energy which is a major need in daily life. Appropriate efforts are needed so that the availability of electrical energy used can be maintained availability. Concern for each consumer in this case a large-scale 1-phase PLN customer, will have a broad impact if they make joint savings through a measurable mechanism for the use of electrical energy. Until now, PLN single-phase customers do not yet have facilities to get real-time information on household electrical energy usage. Thus designed an application that can measure, process data, and display the use of electrical energy which is named